A feasible construction strategy of GO-based hetero-film with long service life at multi-environments: Effective friction transfer application. (April 2022) - Yang, Yawen; Jia, Weihong; Ma, Liming; Zhu, Jinyu; Wang, Honggang; Hou, Kaiming; Wang, Jinqing; Yang, Shengrong
Abstract: In this work, a lubricating hetero-film (GS-PTFE) was constructed through Al 3+ -induced self-assembly of graphene oxide (GO) and SiO2 nanoparticles, and in-situ transfer from polytetrafluoroethane (PTFE) counterpart, which is a simple and surprisingly versatile method. With directly replacing counterpart by GCr15 ball, the tribological results at load of 1 N and frequency of 1 Hz demonstrate that hetero-film exhibits longer wear lives than GS and GO-PTFE film under multi-environments (air, dry N2, humidity), especially not worn out within 1 × 10 4 cycles in 50% humidity. The long durability mainly depends on shielding and lubrication of PTFE, high mechanical strength of GO, rolling effect of SiO2, and secondary transfer film. The transfer lubrication theories of PTFE on GO-based film can offer technical guidance for exploiting high-performance bearing cage. Graphical Abstract: ga1 Highlights: Counterpart replacing strategy is employed to construct GS-PTFE hetero-film. GS-PTFE hetero-film has long service life under air, N2 and humid multi-environments. The lubrication mechanism of PTFE intercalating and shielding was presented. Transfer lubrication offers novel idea for designing bearing cage materials.